Step-by-step explanation:
Consider the following polynomial:
![f\mleft(x\mright)=x^3-4x^2+3x+7](https://img.qammunity.org/2023/formulas/mathematics/college/5z2sriekqts8buwhrcovbiqacbj7dz01av.png)
suppose by contradiction that (x+5) is a factor of the given polynomial f(x). This means that:
![f\mleft(x\mright)=x^3-4x^2+3x+7=(x+5)Q(x)](https://img.qammunity.org/2023/formulas/mathematics/college/z94qvbgd3fo7gg4h83ldqsec1qdhthwche.png)
where Q(x) is another polynomial. Now, according to the above expression if we set f(x)=0, then we obtain:
![x^3-4x^2+3x+7=(x+5)Q(x)=0](https://img.qammunity.org/2023/formulas/mathematics/college/dzhqa4pdnz5vtje8yxxe7pm6ml1n9ldosa.png)
this is true when
![x+5=0](https://img.qammunity.org/2023/formulas/mathematics/college/uilk8umtgf3wsz1raum0x8b3b4lp514728.png)
that is, when:
![x=\text{ -5}](https://img.qammunity.org/2023/formulas/mathematics/college/epu76zge01mk4tgq8fl18fds323rwhosmz.png)
this means that x= -5 is a root of f(x). In other words, this is the same to say that
![f\mleft(\text{ -5}\mright)=0](https://img.qammunity.org/2023/formulas/mathematics/college/uhq2573hivx114f8xwato57ul4vjycs4cg.png)
But this is a contradiction since:
![f\mleft(\text{ -5}\mright)=(\text{ -5})^3-4(\text{ -5})^2+3(\text{ -5})+7=\text{ -233}\\e0](https://img.qammunity.org/2023/formulas/mathematics/college/x0vpbxt8wo4v989f87vv5l2kl5lvlosf1d.png)
then, we can conclude that the expression (x+5) is not a factor of f(x).
Thus, the correct answer is:
Answer:
Since f( -5) is not equal to 0, we can conclude that (x+5) is not a factor of f(x).